Harm Reduction Strategies and Disinhibitors Among Women Who Use Heroin - Kerley, Kent R. (International journal of offender therapy and comparative criminology, 2019)
People who use illicit drugs face significant physical risks in the acquisition, use, and aftermath of their use. This is particularly the case among those who use heroin in view of recent spikes in heroin-associated overdoses, injuries, and deaths. Using a restrictive deterrence framework, we identify the risks that women associate with chronic heroin use and the ways they seek to manage those risks. We also examine psychological and physiological disinhibitors that contribute to women reducing use of risk reduction strategies. We find from the narratives that nearly all of the women initially engaged in specific strategies to manage risk; however, as they continued using the drug, they began to abandon even the simplest of measures. Our findings shed light on the limitations of harm reduction strategies and inform the theoretical tradition of restrictive deterrence and the importance of disinhibitors.